Kenaikan Berat Badan Selama Hamil Dengan Kejadian Preeklamsia - Susanti Pratamaningtyas; Shinta Kristianti; Siti Nurhidayatul Ilma Nafiah (Malang Journal of Midwifery (MAJORY), 2019)
Preeclampsia is a special condition during pregnancy where hypertension and proteinuria occur after 20 weeks of gestation in mothers who have had normal blood pressure. Symptoms that arise in preeclampsia are edema, hypertension, and proteinuria. Caused by many factors, one of which is obesity. Women with bnormal weight have a greater risk of preeclampsia. The purpose of this study was to determine the relationship of weight gain during pregnancy to the incidence of preeclampsia in Gambiran Hospital, Kediri. The sampling technique used was simple random sampling with a population of 117 mothers and a sample of 91 mothers who were in accordance with the inclusion and exclusion criteria, this study was conducted on 6-9 May 2019. The research instrument used was the recapitulation sheet. The results of statistical tests showed that there was a relationship between weight gain during pregnancy and the incidence of preeclampsia in Gambiran Hospital, Kediri City. The Chi Square test results show that the value of ? value is 0.022, then 0.022 <0.05, so it can be concluded that there is a Relationship between Increasing Weight During Pregnancy with the incidence of Preeclampsia in Gambiran Hospital, Kediri City. Suggested for next researchers for to discuss more deeply the causes of the most dominant preeclampsia. Keywords: Peer Education, Reproductive Health, Adolescent Knowledge, Adolescent Attitudes